Pedaling skill training system with visual feedback of muscle activity pattern - Sato, T.; Tokuyasu, T. (Journal of Biomechanical Science and Engineering, 2017)
For cycling competitors, the pedaling exercise is typically accompanied by a binding pedal system. The purpose of this pedal system is to attach the body of the pedal and the sole of the cycling shoe together in order to allow the cyclist to rotate the crank efficiently. Although the importance of a pedaling skill that streamlines the muscle activity of the leg muscles recruited in the pedaling exercise has been widely recognized in the field of cycling, no instructional method based on scientific evidence has been established yet. Hence, this study first proposes an evaluation standard for the pedaling skill by using the muscle activity data of a skilled cyclist. Subsequently, the training system based on the proposed evaluation standard is developed. The system measures the surface electromyogram of the leg muscles and the angle of crank rotation during the pedaling exercise. In addition, the system employs principal component analysis to extract the features of the muscle activity pattern from a beginner and an intermediate cyclist. Furthermore, the online visualization of their pedaling skill, based on the results of the principal component analysis, is implemented to enable cyclists to objectively monitor their pedaling skill. The experimental results obtained from the developed training system and the relationship between the pedaling skill and the consistency of the muscle activity pattern are discussed. The experimental results revealed the significant aspects of the pedaling skills, in which the consistency of the muscle activity pattern and the motion of pulling the pedal up were relatively clear in the pedaling of the skilled cyclist.